CZY ISTNIAŁA KULTURA BROMME? - Kobusiewicz, Michał (Wydawnictwo Naukowe UAM, 2009)
Substantial progress in the Final Palaeolithic studies in Central and Eastern Europe over the last three decades sheds a new light on the problem of the Bromme culture. It turned out that the Lyngby points, known also as ‘fossile directeur’, have been found in a large number far away from the core area of the Bromme culture. Their presence in these areas has been interpreted by many scholars as an indication of arrival of the groups from southern Scandinavia. However, detailed analysis of these projectile points indicates that they comprised an excellent and efficient hunting weapon commonly adopted by all tundra hunters. By no means they can be treated as a cultural marker. Moreover, it is not at all clear whether the Bromme culture existed? Majority of studies used to focus upon flint artefact typology. However, its heuristic potential in the discussed area has been exhausted and its further continuation is counterproductive. Alternative research strategy is needed aimed at recognition of cultural differentiation in Final Palaeolithic and Mesolithic along with different aspects of hunter-gatherers existence such as subsistence pattern, space organisation in settlement, social organisation, spiritual life, anthropological structure, etc. This new approach is the only means of objective reconstruction of cultural differentiation of the oldest periods of the European prehistory.
WHETHER THE BROMME CULTURE EXISTED?